InGaN super-lattice growth for fabrication of quantum dot containing microdisks - El-Ella, H; Rol, F; Collins, D; Kappers, M; Taylor, R; Hu, E; Oliver, R (2011)
Microstructural characterisation of a heterostructure containing an In xGa1-xN/InyGa1-yN super-lattice sacrificial layer (SSL), an AlGaN etch stop layer and an InGaN quantum dot layer has been carried out. These structures are intended for photo-electrochemical etch mediated fabrication of undercut microdisks and were found to generate additional dislocations due to the additional strain energy imposed by the growth and inclusion of the InGaN quantum dot layer. Micro-photoluminescence was also carried out and showed the unexpected formation of quantum dots within the SSL. An equilibrium critical stack thickness model corresponding to the total thickness of the heterostructure that would favour the additional generation of dislocations was formulated through an energy-balance consideration. This correlated well with the experimental results and a prediction of the SSL indium composition for the full structure that would not lead to additional dislocation generation could thus be made. © 2011 Elsevier B.V. All rights reserved.